2015
DOI: 10.21608/ejnf.2015.104663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplement Green Tea and Tetracycline on Nutrient Digestibility, Some Blood Metabolites and Growth Performance of Growing Buffalo Calves

Abstract: he current study was conducted to investigate the effect of addition green tea and tetracycline hydrochloride or both of them to growing buffalo rations on digestibility, blood metabolites and animal performance. Twelve buffalo calves of 11-13 months of age weighing 213 ±3.52 kg were divided into 4 groups of 3 animals each. Dried green tea was added to calves in basic diet (control) at levels of 0.5 % (T1), 1 % tetracycline hydrochloride (T2), and 1 % dried green tea and 1% tetracycline hydrochloride (T3) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The observed increase in plasma protein concentration in the sheep can be attributed to the relatively higher crude protein content present in the bamboo leaves used as a supplement in the grass basal diets. Previous studies have indicated a positive correlation between dietary protein and plasma protein concentrations (Yousef and Zaki, 2001;Shahen et al, 2004). This correlation was particularly evident in diets containing O. abyssinica supplements, known for their higher crude protein content, thereby rendering a net positive plasma protein balance in the blood of the host sheep.…”
Section: Effect Of Bamboo Leaf Supplementation On Serum Metabolites O...mentioning
confidence: 80%
“…The observed increase in plasma protein concentration in the sheep can be attributed to the relatively higher crude protein content present in the bamboo leaves used as a supplement in the grass basal diets. Previous studies have indicated a positive correlation between dietary protein and plasma protein concentrations (Yousef and Zaki, 2001;Shahen et al, 2004). This correlation was particularly evident in diets containing O. abyssinica supplements, known for their higher crude protein content, thereby rendering a net positive plasma protein balance in the blood of the host sheep.…”
Section: Effect Of Bamboo Leaf Supplementation On Serum Metabolites O...mentioning
confidence: 80%
“…In the same study similar to our results the GH concentrations were determined the highest values in essential oregano oil group. In a different study, Hassan & Hassan, (2009a) reported that Karadi lambs fed diet supplemented with rosemary significantly increased GH and daily gain compared with fed except rosemary additive.…”
Section: Discussionmentioning
confidence: 93%